The potential impact of New Zealand-China free trade agreement on New Zealand's textile, clothing and footwear industries : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Economics at the Department of Applied and International Economics,Massey University - Hong, Zuwen (Massey University, 2005)
The New Zealand and Chinese governments are currently negotiating a Free Trade Agreement (FTA). The proposed FTA would provide a basis for a significant expansion of trade between New Zealand and China. According to the joint feasibility study by the New Zealand Ministry of Foreign Affairs and Trade and the Chinese Ministry of Commerce, both countries will gain at the macro level of economic activities. However, the potential impact on specific industries will be different. Textiles, clothing and footwear industries in New Zealand have undergone significant contraction since the country's trade liberalisation and reduction in protection in the mid-1980s. More recently, these industries in New Zealand have achieved dramatic restructuring and rationalisation in the process of adopting trade liberalisation and the reduction in protection. Nevertheless, the industries are the few that still have relatively highly tariffs in New Zealand. Given the outstanding performance of China's textiles, clothing and footwear industries, the future of the textiles, clothing and footwear industries in New Zealand would be hard to predict. This thesis examines the potential impact of the proposed Free Trade Agreement (FTA) between New Zealand and China on the textiles, clothing and footwear industries in New Zealand. A survey method was used for the purpose of this study. Firstly, the recent performance of the textiles, clothing and footwear industries in New Zealand and China and the two way trade between the two nations were analysed in detail to provide the basis for the assessment of the potential impacts under the context of the proposed FTA. Next, to examine such potential impact directly, a sample of 15 textiles, clothing and footwear firms currently operating in New Zealand was selected. Qualitative information, including threats, opportunities and firms' response strategies arising from a NZ-China FTA, was obtained through interviewing each firm's senior executives. The results of this study show that New Zealand's trade liberalisation since the mid-1980s has yielded a substantially more competitive and productive industry base. Trade liberalisation and reduction in protection since the mid-1980s has forced many textile, clothing and footwear (TCF) firms to exit the industry, so the survivors are all relatively strong players in their respective niche markets. However, a further contracting of the industries in terms of manufacturing capability will be inevitable in the environment of a free trade deal with China, given the rapidity of China in expanding its production and lowering its prices and the intrinsic disadvantage of TCF industries in New Zealand. The employment in TCF manufacturing will further decline. The bilateral free trade with China would further reinforce the need for New Zealand TCF industries to continue to restructure and to move into design-based, high-end merchandise with a niche market focus. The findings of this study highlight two directions of future TCF industries in the context of an FTA with China: firstly, the future of New Zealand TCF industries will be one in which changes will be driven by design talent, technology and speed to market. Secondly, another possible way out for New Zealand TCF industries lies in the management of markets, organizing a global supply chain of subcontractors and in retailing.
Keywords: Clothing trade; Textile industry; Footwear industry; Free trade agreement; New Zealand trade with China